Pharmacokinetics of Pentoxifylline after Oral Administration of a Sustained Release Tablet at Two Different Times of the Day - Srinivasu, Poondru; Rambhau, Devraj; Rao, Boinpally Ramesh; Rao, Yamsani Madhusudan (Arzneimittelforschung, 1999)
The pharmacokinetics of pentoxifylline (CAS-6493-05-6) was studied in healthy subjects by orally administering a 400 mg sustained release tablet (Trental®) at two different times (10:00 or 22:00 h) of the day in a crossover design. Pentoxifylline concentrations in serum samples were estimated by using high performance liquid chromatography. The mean values of Cmax (326.38 ± 39.77 vs 266.35 ± 36.0 ng/ml, p < 0.01, n = 8), AUC0–t (2424 ± 382 vs 2141 ± 300 ng/ ml/h, p < 0.05, n = 8) were significantly higher and Vss/f (16537 ± 2869 vs 20136 ± 5006 ml/ kg), Vd/f (11807 ± 2704 vs 15801 ± 5960 ml/kg) were significantly (p < 0.05, n = 8) lower following morning (10:00 h) administration than in the night (22:00 h). These variations should be considered while designing sustained release dosage forms.
Keywords: CAS 6493-05-6; Pentoxifylline; Trental®, circadian variations, healthy; volunteers, pharmacokinetics, sustained release tablet